Pemanfaatan Aplikasi You Tube Sebagai Media Pembelajaran Bahasa Indonesia - Yusriani Yusriani; Masriyanti Nasution; Edi Syahputra (Universitas Dehasen Bengkulu, 2022)
The purpose of this study is to explain the use of the YouTube application as a medium for learning Indonesian. This study used a qualitative descriptive research design. The subject of this research is the YouTube application, and the subject of the research is the use of the YouTube application as a medium for learning Indonesian. Data was collected by observation method and then through descriptive analysis using equipment in the form of documentation and documented records. Second, the data analysis phase includes data reduction, data presentation, and drawing conclusions. And the survey results show that the YouTube application is used in combination with the correct use and method. Useful as a medium for learning Indonesian in an interesting way. This application is very simple and there are various types that display various types of very detailed information so that you can apply your YouTube application while learning Indonesian. Further research is needed to find out how effective the Youtube application is in improving student learning outcomes in Indonesian subjects.